Electrophysiological Investigation of the Subcellular Fine Tuning of Sympathetic Neurons by Hydrogen Sulfide - Dominguez-Rodriguez, Manuel; Drobny, Helmut; Boehm, Stefan; Salzer, Isabella (Frontiers in Pharmacology, 2017)
H2S is well known as hypotensive agent, whether it is synthetized endogenously or administered systemically. Moreover, the H2S donor NaHS has been shown to inhibit vasopressor responses triggered by stimulation of preganglionic sympathetic fibers. In contradiction with this latter result, NaHS has been reported to facilitate transmission within sympathetic ganglia. To resolve this inconsistency, H2S and NaHS were applied to primary cultures of dissociated sympathetic ganglia to reveal how this gasotransmitter might act at different subcellular compartments of such neurons. At the somatodendritic region of ganglionic neurons, NaHS raised the frequency, but not the amplitudes, of cholinergic miniature postsynaptic currents via a presynaptic site of action. In addition, the H2S donor as well as H2S itself caused membrane hyperpolarization and decreased action potential firing in response to current injection. Submillimolar NaHS concentrations did not affect currents through Kv7 channels, but did evoke currents through KATP channels. Similarly to NaHS, the KATP channel activator diazoxide led to hyperpolarization and decreased membrane excitability; the effects of both, NaHS and diazoxide, were prevented by the KATP channel blocker tolbutamide. At postganglionic sympathetic nerve terminals, H2S and NaHS enhanced noradrenaline release due to a direct action at the level of vesicle exocytosis. Taken together, H2S may facilitate transmitter release within sympathetic ganglia and at sympatho-effector junctions, but causes hyperpolarization and reduced membrane excitability in ganglionic neurons. As this latter action was due to KAT P channel gating, this channel family is hereby established as another previously unrecognized determinant in the function of sympathetic ganglia.